Growth Assessment of Tree Species Growing in the Amhara Region in Ethiopia. (21st October 2022) - Yosef, Binyam Alemu; Hasenauer, Hubert; Pötzelsberger, Elisabeth
ABSTRACT: Ethiopian mixed forests have multipurpose benefits and services. However, there is a gap of information in the entire Ethiopian highlands on forest growth needed for implementation of sustainable forest management and provision of ecosystem services. Therefore, main aim of this study was to identify main factors deriving tree growth in forest and woodland in Amhara Regional State of Ethiopia and to provide an individual tree basal area increment (BAI) model based on increment cores. The data came from 170 sampling plots in study area and cover 51 tree species. For each tree species, diameter at breast height (DBH), height, increment core measurement, tree location, and distance from subject tree measurements were recorded. Because of large number of trees species, it is difficult to develop growth functions for each individual tree species. Thus, classification of species groups provided a framework to organize information that differs between vegetation types. Our classification resulted in three groups. For each tree species group, an individual tree BAI model was calibrated. The tree species group of BAI differs by DBH class. The response to BAI depends on competitive condition of a tree. This growth model can be used to predict tree growth for Ethiopian mixed-species forests.